PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Sasanti, Elin Erlina; Animah, Animah; Fikri, M Ali (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2023)
This study aims to examine the effect of Corporate Social Responsibility on company value with corporate governance as a moderation Variable. The grand theory used in this study is legitimacy theory, stakeholders, and agency theory. This type of research is descriptive quantitative. The data source obtained is sourced from secondary data obtained from www.idx.co.id. The research population is manufacturing companies going public in 2018-2020. Purposive sampling technique with a total sample of 54. The analysis tools used are moderate regression analysis. The results showed that CSR, company values, Corporate Governance have no effect on company value. Meanwhile, the study found that corporate governance does not strengthen or weaken the relationship between CSR and company values. The implication of this study is that during a pandemic it is rather difficult to predict from the financial side, this is due to the high uncertainty factor, even though the company already managed very well.